2022
DOI: 10.1073/pnas.2201014119
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical frustration of phase-separated domains inCoscinodiscusdiatom frustules

Abstract: Diatoms are single-celled organisms with a cell wall made of silica, called the frustule. Even though their elaborate patterns have fascinated scientists for years, little is known about the biological and physical mechanisms underlying their organization. In this work, we take a top-down approach and examine the micrometer-scale organization of diatoms from the Coscinodiscus family. We find two competing tendencies of organization, which appear to be controlled by distinct biological pathways. On one hand, mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…(ii) Previously, it has been assumed that silica morphogenesis inside the valve SDV is dependent on directional influx of silica precursor [47]. Similarly, it was proposed that cytoskeletal fibers may guide pattern formation [26], [48]. While the cytoskeleton could contribute to material delivery to the SDV and determining SDV shape, our model shows that neither directed silica influx nor a direct guidance role of cytoskeletal fibers is required to explain the formation of radial rib patterns.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…(ii) Previously, it has been assumed that silica morphogenesis inside the valve SDV is dependent on directional influx of silica precursor [47]. Similarly, it was proposed that cytoskeletal fibers may guide pattern formation [26], [48]. While the cytoskeleton could contribute to material delivery to the SDV and determining SDV shape, our model shows that neither directed silica influx nor a direct guidance role of cytoskeletal fibers is required to explain the formation of radial rib patterns.…”
Section: Discussionmentioning
confidence: 58%
“…This yields N b (r) = N b (0)+2π r/d for the expected number of branching points in a valve of area A = π r 2 , up to a constant offset N b (0) which corresponds to stem branching points of the annulus. A similar geometric law was previously applied to the number of defects in pore patterns of diatom valves [26]. Mathematical description.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples include the photonic structures generating color in some bird feathers, [15][16][17][18] the topography of pollen's cell walls, [19] and the regular porosity of diatom frustules. [20][21][22] We have previously shown that polymerization-induced phase separation in the solid state can be used to make durable, nanostructured, and colorful materials. [23] This process starts with a glassy polymer matrix swollen and plasticized with a second monomer.…”
Section: Macromolecular Materials Often Possess Highly Desirablementioning
confidence: 99%
“…For example, cells generate structures with pronounced order and low size dispersity through phase separation. Some examples include the photonic structures generating color in some bird feathers, [15–18] the topography of pollen's cell walls, [19] and the regular porosity of diatom frustules [20–22] . We have previously shown that polymerization‐induced phase separation in the solid state can be used to make durable, nanostructured, and colorful materials [23] .…”
Section: Figurementioning
confidence: 99%